Analysis of Employee Performance Influenced by Employee Engagement and Employee Competency Mediated by Work Motivation at RSHC - Istiqomah, Sarah Nabila; Tj, Hery Winoto; Saparso, Saparso (Syntax Corporation, 2026)
The growth of technology requires organizations to manage human resources more effectively to achieve optimal performance. This study aims to analyze the influence of employee engagement and employee competence on performance with work motivation as an intervening variable in RSHC. This study uses a quantitative approach with a survey method. The research population amounted to 242 employees, and the sample was determined by purposive sampling of 100 respondents who were permanent employees with a minimum working period of two years. Data collection was carried out through a Google Form-based questionnaire with a Likert scale. Data analysis used outer model test, inner model test, and hypothesis test. Data analysis was carried out with the help of Structural Equation Modeling–Partial Least Square (SEM-PLS) software through SmartPLS 4 software. The results of the study show that: (1) employee engagement has no effect on performance; (2) employee competence has a positive effect on performance; (3) employee engagement has no effect on work motivation; (4) competence has a positive effect on work motivation; (5) work motivation has a positive effect on performance; (6) motivation does not mediate the relationship between employee engagement and performance; and (7) motivation mediates the relationship between competence and performance, showing that good competence can increase motivation and further encourage improvement in employee performance.